Female athletes' knowledge of biopsychosocial puberty-related topics in sports. What is missing? - Radovan, F.; Solstad, B. E.; Kjær, J. B.; Melin, A.; Ausland, Å.; Bjärsholm, D.; Ivarsson, A.; Torstveit, M. K.; Laxdal, A.; Augustsson, S. R.; Linner, S (Frontiers in Sports and Active Living, 2025)
Introduction: Puberty has been identified as one of the main contributing factors for girls dropping out of sports during adolescence. Knowledge and social support can, however, help athletes navigate the biopsychosocial (BPS) puberty-related changes associated with this period. Yet, research on female athletes' knowledge about BPS puberty-related topics is lacking. Therefore, this cross-sectional study aimed to examine female athletes' perceived knowledge and knowledge needs of BPS puberty-related topics during adolescence, explore interconnections across BPS domains, and investigate differences between athletes in team and individual sports.